Growth of chemical gardens in gaseous acidic atmospheres. Issue 11 (19th January 2023) - Angelis, Georgios; Sant, Georgios; Vizirianakis, Ioannis S.; Pampalakis, Georgios
Abstract : Laboratory calthemites. The growth of chemical gardens at the liquid-air interface is demonstrated that yields analogues of calthemites and soda straws. Abstract : The generation of chemobrionic architectures through slow injection of aqueous silicate solution in gaseous TiCl4 is demonstrated. The tubes were characterized by XRD, SEM and wet chemistry control experiments, and their mechanism of formation was unraveled. These structures serve as laboratory models for calthemites or soda straws.